2019
DOI: 10.1016/j.ijpharm.2018.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel zero-order release budesonide tablets for the treatment of ileo-colonic inflammatory bowel disease and comparison with formulations currently used in clinical practice

Abstract: Development of novel zero-order release budesonide tablets for the treatment of ileo-colonic inflammatory bowel disease and comparison with formulations currently used in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Current therapies for IBD, however, are also pursuing intestine-specific delivery of drugs. The ColoPulse technology is such a novel approach which allows controlled release of drugs at the terminal ileum and colon [45]. Systemic and gastrointestinal side effects of pirfenidone may be minimized using such approach, concomitant with a higher drug-efficacy of pirfenidone on intestinal inflammation and fibrosis [46].…”
Section: Discussionmentioning
confidence: 99%
“…Current therapies for IBD, however, are also pursuing intestine-specific delivery of drugs. The ColoPulse technology is such a novel approach which allows controlled release of drugs at the terminal ileum and colon [45]. Systemic and gastrointestinal side effects of pirfenidone may be minimized using such approach, concomitant with a higher drug-efficacy of pirfenidone on intestinal inflammation and fibrosis [46].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, new coating technology has been actively pursued to improve the targeting effectiveness of pH-dependent delivery systems. For example, ColoPulse technology is an innovative pH responsive coating technology, which incorporates super-disintegrant in the coating matrix to accelerate the disintegration at the target site [50][51][52]. The incorporation of a super-disintegrant in a non-percolating mode leads to a more reliable and pulsatile drug release.…”
Section: Tablets and Capsulesmentioning
confidence: 99%
“…Furthermore, food and time of food intake did not affect the targeting effectiveness of ColoPulse delivery systems [51]. Recently, Gareb et al [52] adopted this technology to develop the ileo-colonic-targeted zero-order sustained-release tablets of budesonide for the topical treatment of IBD. The results indicated that drug release from the developed tablet began in the simulated ileum, and the release rate remained constant throughout the entire simulated colon [52].…”
Section: Tablets and Capsulesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of conventional drug delivery systems in IBD is limited, since they lead to systemic absorption of the drug, with related side effects and toxicity [4], such as osteoporosis and osteonecrosis, adrenal suppression, diabetes, cataract and glaucoma, as well as gastro-intestinal, cutaneous and cardiovascular complications [5]. As a consequence, several innovative drug delivery systems have been developed to achieve a selective drug delivery to the inflamed tissues [6][7][8][9]. With this aim, several approaches can be followed, i.e., the use of prodrugs becoming active after the hydrolysis by specific colon enzymes [10], bioadhesive delivery systems [11], timed-dependent delivery systems [12] and drug coating with pH dependent polymers [13,14].…”
Section: Introductionmentioning
confidence: 99%